147 - THE CHALLENGES OF HOME EDUCATION IN BRAZIL (Fiep Bulletin - online, 2011)
The internal and external evaluations related to Brazilian education point to alarming and worrisome when it comes to developing skills reading, writing or math students, which grows in Brazil, mostly underground, the type of education called Home Education. For legal scholars, such secrecy only occurs because the constitution of Brazil was made in a time when there was a need for such discussion, and that after 20 years, today, many other demands on society. Adopted in several countries such as Canada, England, Mexico, Germany and some states of the United States of America brings about more than 2 million children around the world. The results indicate that practice in favour of its adherents than the cognitive aspect, the fact that these children to integrate easily into a variety of social backgrounds and are accustomed to take responsibility within their families what they motivate themselves in their day the day. Children benefited from the freedom to develop their skills at their own pace through a flexible approach, as well as receiving a high level of parental attention. The input of parents and commitment, regardless of their socioeconomic status and educational level, may be the most important factor in child development and its progress.
Keywords: Education; Home Education; Challenges